2013
DOI: 10.11564/27-1-4
|View full text |Cite
|
Sign up to set email alerts
|

Regional variation in neonatal and post-neonatal mortality in Kenya

Abstract: This paper seeks to establish the effect of region of residence on neonatal and post-neonatal mortality in Kenya, using

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
1
3
1
Order By: Relevance
“…Contrary to the findings of other studies (Zahid, 1996;Mahmood, 2002;Ikamari, 2013) this study found that antenatal care provider, tetanus injection during pregnancy, place of delivery and birth delivery assistants have no effect on under-five mortality in Zimbabwe in the multivariate level analysis. However, the direction of the relationship between antenatal care, birth delivery assistants and under-five mortality shows that use of an unskilled antenatal provider and the presence of an unskilled birth attendant during delivery increase the risk of a childhood death occurring.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to the findings of other studies (Zahid, 1996;Mahmood, 2002;Ikamari, 2013) this study found that antenatal care provider, tetanus injection during pregnancy, place of delivery and birth delivery assistants have no effect on under-five mortality in Zimbabwe in the multivariate level analysis. However, the direction of the relationship between antenatal care, birth delivery assistants and under-five mortality shows that use of an unskilled antenatal provider and the presence of an unskilled birth attendant during delivery increase the risk of a childhood death occurring.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, the risk of neonatal death was more likely to occur among neonates from the poorest family as compared to the richest family. This result is consistent with previous studies conducted in Nigeria [18], Kenya [19], and Sudan [20]. This occurs may be due to families with high-income levels might get necessary health services during pregnancy, delivery and after delivery, and the neonates might be provided better care than a family with low income [21].…”
Section: Plos Onesupporting
confidence: 91%
“…Another environment-related factor that has been found to exhibit pronounced variations in child survival is region (geographical location of residence) and ethnicity. Regional differentials have been documented in many African countries including Nigeria (Adetunji, 2002;Ikamari, 1995;Kuate-Defo, 1996;Manda, 1999). Some of the regional differences found in previous studies were claimed to be due to http://aps.journals.ac.za/ differences in climate/weather, household environmental factors, socio-economic and cultural factors (Adebayo and Fahrmeir, 2005;Kandala et al 2007).…”
Section: Environmental Factorsmentioning
confidence: 97%